2014
DOI: 10.1099/mic.0.074146-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of phosphate solubilization and antifungal activity of Streptomyces spp. isolated from wheat roots and rhizosphere and their application in improving plant growth

Abstract: The application of plant-growth-promoting rhizobacteria (PGPR) at field scale has been hindered by an inadequate understanding of the mechanisms that enhance plant growth, rhizosphere incompetence and the inability of bacterial strains to thrive in different soil types and environmental conditions. Actinobacteria with their sporulation, nutrient cycling, root colonization, bio-control and other plant-growth-promoting activities could be potential field bio-inoculants. We report the isolation of five rhizospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
133
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(151 citation statements)
references
References 50 publications
7
133
1
3
Order By: Relevance
“…Plant growth promotion can be achieved through solubilization of inorganic phosphates by these organic acids. de Werra et al showed that this happens with not only gluconate but also malate [42,43]. These results were consistent with earlier report on the P and Zn solubilizing properties of Acinetobacter sp.…”
Section: Phosphate Solubilization and Mineralizationsupporting
confidence: 83%
See 2 more Smart Citations
“…Plant growth promotion can be achieved through solubilization of inorganic phosphates by these organic acids. de Werra et al showed that this happens with not only gluconate but also malate [42,43]. These results were consistent with earlier report on the P and Zn solubilizing properties of Acinetobacter sp.…”
Section: Phosphate Solubilization and Mineralizationsupporting
confidence: 83%
“…Inoculation of efficient plant-growth-promoting actinobacterial Streptomyces species significantly improved the Fe, Mn and P content of wheat plants when compared with an uninoculated control [43,105]. Yasin et al investigated the effects of selenate fertilization and bacterial inoculation on Se uptake and plant growth [122].…”
Section: Pgpr and Plant Nutrient Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…were implicated in anti-fungal activities by Jog et al (2014), where studies showed that Streptomyces strain that inhibits the growth of fungal pathogens produces this low molecular mass compound. However, compare to the GC-MSD profile of the Streptomyces strain in Jog et al (2014), the level of detection for pyrrolo (1, 2a) pyrazine, 1,4-dione hexahydro-3-(2 methylpropyl) is higher compared to T. virens 159c. Another compound known as dl-mevalonic acid lactone was identified in fraction 4.…”
Section: Table 3 Metabolites Identified From Fraction 4 Of Trichodermentioning
confidence: 99%
“…Esses mecanismos de ação posicionam as Actinobactérias entre o grupo das Rizobactérias Promotoras do Crescimento em Plantas (RPCPs), mais importantes da rizosfera se destacando por estimular o crescimento vegetal e diminuir a invasão de microrganismos fitopatógenos nas plantas com as quais se associam (Beneduzi et al 2013). Dentre os mecanismos indiretos que podem exercer as Actinobactérias para o controle de microrganismos fitopatógenos, além da indução de resistência, encontra-se a solubilização de fósforo, principalmente associado à produção de ácidos orgânicos, como os ácidos cítrico, glucônico, láctico, málico e oxálico (Chen et al, 2006;Jog et al, 2014). A liberação desses ácidos já foi descrito para alguns gêneros de Actinobactéria, como é o caso de Streptomyces em solos com deficiência de fósforo em cultivos de trigo (Hamdali et al, 2008).…”
Section: Introductionunclassified